". DET BESTE I DEN NORDNORSKE FORTELJARTRADISJONEN". Om Lars Bergs romaner – sammenliknet med Hamsuns - Wærp, Henning Howlid (Nordlit, 2016)
Published version. Source at http://doi.org/10.7557/13.3756 . License CC BY 4.0 . This article uses a regional perspective to compare the novels of Lars Berg with Knut Hamsun’s novels set in northern Norway. What characterizes the northern Norwegian storytelling tradition, and is it possible to define it? In order to close in on this concept, this article focuses on certain aspects of setting, including: fishery, trade, language, and character.